THE EFFECTIVENESS OF TEACHING PRONUNCIATION THROUGH JAZZ CHANTS METHOD - Nurhayati, Nurhayati; Nurhamdah, Nurhamdah (Inspiring: English Education Journal, 2019)
This study expected to find out the effectiveness of teaching pronunciation through jazz chants and the students? response toward the implementation of jazz chants method in teaching pronunciation at the eight grade of MTsN Parepare. The result of this research was expected to be useful information in the English teaching and learning process especially in the pronunciation teaching. This research applied pre-experimental method, with two group pre-test and post-test design. The samples of the research were consisted of 27 students from five classes taken from the population at the eight grade students of MTsN Parepare first semester in Academic Year 2018/2019.The result of the data analysis showed that the students? pronunciation abilitywas improved. It could be showed from the result of the t-obtained value (7.698) was higher than t-table value (1.706). Those indicated that H0 was rejected and Ha was accepted. It meant that the students? pronunciationwas able increased by using jazz chants method. Besides that, the result of the questionnaire showed that most of the students agree and had a positive response in learning pronunciation by using jazz chants method. It could be showed from the result of the cumulative percentage on the fifteen items of the questionnaire was 89,28 (very strong), while the cumulative score that they got the questionnaire was 1808 (strongly agree). Based on the result of data analysis above, the researcher then concluded that the students? pronunciation ability was improved and it is effective to teaching pronunciation through jazz chants at the eight grade of MTsN Parepare.